Composition, structure and dynamics of natural regeneration over 18 months of study in understory of Pinus elliottii Engelm (Research, Society and Development, 2022)
The study of the dynamics of natural regeneration in understory of Pinus elliottii Engelm assistis in strategies of management, conservation and improvement of conditions for natural regeneration of native understory species. In this sense, there is the hypothesis of using this understory to provide environmental services and providing indicative data on the degree of disturbance generated by the canopy of the exotic species, which may suggest coexistence between the exotic species and the native regenerating species. The present study aimed to characterize the natural regeneration of understory of P. elliottii and to verify the dynamics of regeneration with the presence of this species over the course of 18 months of study. To characterize the understory vegetation of P. elliottii, 24 plots of 40x5 m were allocated. To monitor the regeneration dynamics were analyzed 8 subplots of 5x5 m. Variations in the number of individuals and species, the number of individuals separated by pioneers and non-pioneers, and pine individuals were tested for homogeneity by Bartlett's test. The averages were compared by Tukey test (5% probability) and the phytosocilogical parameters were analyzed to understand the vegetation structure. There was a predominance of species and non-pioneer individuals, highlighted the families Lauraceae and Myrtaceae. There were no changes in the evolution of the dynamics of understory natural regenerants during the study period, however, the presence of the exotic species shaped the expression of regeneration, in view of the predominance of species and families with characteristics of more advanced successional phases.